PENGARUH RELAKSASI PERNAPASAN DAN TERAPI MUROTAL TERHADAPNYERI PERSALINAN KALA 1 - Reni Syafitriati; Riza Savita (Jurnal Ilmiah Citra Kebidanan, 2026)
Pain during the first stage of labor was an uncomfortable sensation arising from the physiological process of childbirth, particularly during the cervical dilation phase until full dilation (10 cm). This pain was multifactorial, originating from strong uterine contractions, pressure on the cervix, and the stretching of birth canal tissues. The purpose of this study was to determine the effect of a combination of breathing relaxation techniques and murotal therapy on pain intensity during the first stage of labor at Kelapa Community Health Center in 2025. This research was a quantitative study with a Quasi-Experimental design using the One Group Control Pre-Post Test Design approach. The population of this study consisted of all mothers who gave birth in the PONED delivery room at Kelapa Public Health Center during one year, ending in 2024. The sample consisted of 69 respondents, selected using a purposive sampling technique. Data were analyzed using the paired t-test. The results showed a significant decrease in pain intensity among mothers during the first stage of labor after receiving the intervention. The mean pain scale before the therapy among laboring mothers at Kelapa Public Health Center was 3.45 with an SD of 0.501, while after the intervention, the mean pain scale decreased to 1.64 with an SD of 0.484. Statistical analysis using the paired t-test showed a p-value of 0.000 (p < 0.05).